Direct ink write 3D printing of wave propagation sensor. (1st December 2022) - Hassan, Md Sahid; Zaman, Saqlain; Rodriguez, Aaron; Molina, Laura; Dominguez, Cesar Enrique; Morgan, Robert; Bernardin, John; Lin, Yirong
Abstract: The ability to detect impact waves and their propagation across materials is the key to structural health monitoring and defect detection of materials. To detect impact waves from a certain type of structures, it is important for a sensor to be highly flexible and complex in shape. Direct ink write (DIW) allows for the manufacturing of complex sensors. This article presents the fabrication of a flexible impact wave propagation sensor (IWPS) through the DIW technique. The dispersion of a ferroelectric ceramic material barium titanate (BaTiO3, or BTO) in polydimethylsiloxane (PDMS), not only enhances the flexibility of the 3D (three-dimensional) printed sensor but also ensures the uniform piezoelectric response throughout the whole sensor. This research explored the impact load generated impact wave in the flexible sensor and sensing response. The capability of DIW for multi-material printing was utilized to print multi-walled carbon nanotube based electrodes on BTO/PDMS stretchable composites. A total of 50 wt% of BTO in the PDMS matrix resulted in a piezoelectric coefficient of 20 pC N −1 after contact poling of IWPS. Upon applying impact loading at the center of the sensor, an impact wave was generated which gradually diminished with the distance from the origin of the applied impact load. The impact wave propagation was quantitatively characterized by measuring output voltage from different nodes of IWPS. Additionally, from the voltage response time difference at different locations of the sensor, the particle-wave velocity of a certain material attached to IWPS was determined in this research. Using the custom-designed IWPS, it was found that the particle-wave velocity of stainless steel and low-density polyethylene were 5625 m s −1 and 2000 m s −1 respectively, which are consistent with their theoretical values.